Low-cost software proposal for integrated business management (Research, Society and Development, 2020)
This work is dedicated to the elaboration of a computational program developed in the VBA language, in order to facilitate the resolution of problems in the business environment. It aims at being an alternative in the face of difficulties for small and medium-sized companies to remain in the market. The use of this tool assists in management as a whole: people, financial, inventory and supplier business management. To meet the proposal of this work, a logical structure was created for the development of the model, in addition to the program interface, from an ergonomic point of view. The software's performance was satisfactory from a simulated situation of a fictitious company. The application developed in this work meets the expectations of small and medium-sized companies, as it is an effective application to aid decision making and free of acquisition and implantation costs.